Real time analysis of fetal phonocardiography - Tan, B.H.; Moghavvemi, M. (2000)
A simple, low cost and non-invasive PC-based system that is capable of processing real time fetal phonocardiographic signal was developed. The hardware of the system mainly consists of two modules: the front-end module and the data acquisition & control module. The front-end module is mainly used for heart sound signal capturing and conditioning. A new electronic stethoscope with enhanced performance was also developed. The audio output unit enables the system to provide simultaneous listening and visual representation of the heart sound. The data acquisition and control module offers a 4-channel analog multiplexer, a programmable gain amplifier, and a 12-bit resolution ADC. Various sampling rates can be provided through the programmable timer. A Windows 95-based software processes the real time heart sound signal. Both time varying amplitude graph and power spectral plot (based on 512-point Fast Fourier Transform, FFT) can be shown simultaneously on a channel's view. The software is capable of showing all four channels' views on the computer screen at the same time. Thus, enabling multichannel concurrent analysis on the signals.